The difference between metacognition and mindreading: Evidence from functional near-infrared spectroscopy - Li, Zhaolan; Dai, Wenwu; Jia, Ning (Frontiers in Psychology, 2022)
The relationship between metacognition and mindreading was investigated by examining how well one can monitor their own learning (Self) compared to another person’s learning (Other). Here, we used functional near-infrared spectroscopy (fNIRS) to systematically investigate the brain area activation during metacognition and mindreading. The evidence indicates that metacognition and mindreading are underpinned by distinct neural systems. Metacognition is associated with activation in brain regions important for memory retrieval, such as the fusiform gyrus, while mindreading is associated with activation in brain regions important for understanding and reasoning about others' intentions, such as the right temporoparietal junction (rTPJ).